A few more words about the name Elżbieta - Żuraszek-Ryś, Iwona (Name – style – text: A jubilee book dedicated to Professor Elżebieta Umińska-Tytoń, 2023)
Elżbieta is the name of biblical origin, and its appearance in Polish anthroponymy should be associated with the expansion of Christian culture, which in the Middle Ages covered almost all of Europe. It is a name taken from the Hebrew language. In Poland this name has been known since the 13th century. The first record of the name can be found in the document from 1198, then in the form Helisabeth: „Mesacho, Pollonie dux et prima uxor eius Helisabeth. For many centuries it was the name of a very popular, but since the sixties of the 20 th century, its popularity is decreasing.